Analisis Pola Penggunaan Tagar Viral sebagai Media Pendidikan Karakter Netizen (Studi Kritis pada Fenomena Global mengenai Tagar #dajjal di Twitter) - Purwati Purwati; Eldi Mulyana; Nuraly Masum Aprily (Journal Civics and Social Studies, 2021)
ABSTRACTHashtag plays a role as the key to global social change while education plays a role as a tool to optimize it. A topic discussed in this study is that a research on viral hashtag has not been found as a medium for character education for netizens. The research problems formulated in this study are viral Twitter hashtags and the concept of viral hashtags as a medium for character education for netizens. This study aims to determine the patterns of viral hashtags on Twitter and to find out the concept of viral hashtags as a medium for character building for netizens. This study has the benefit of complementing the concept of character education in the technology era and helping people become netizens with character. The research used a qualitative approach with discourse analysis. The objects of this study are viral hashtags, while the subjects are netizens. The samples of this study are the hashtag #dajjal found on Twitter. The instruments used are observation and document notes. The data dealing with character education were analyzed and triangulated. The results of this study show that: 1) viral hashtags are used to share knowledge, pray, opinions, discussions, social movements, peace mediators, entertainment, and personal interests; 2) the concept of character education for netizens, namely viral hashtags as a medium for conveying knowledge, expression, declaration, clarification, action, and control values.Keywords: hashtags, media, character education, netizens, Twitter ABSTRAKTagar sebagai kunci perubahan sosial global dan pendidikan sebagai alat untuk mengoptimalnya. Masalah penelitian pada kajian ini yaitu belum ditemukan penelitian tagar viral sebagai media pendidikan karakter bagi netizen. Rumusan masalahnya adalah pola penggunaan tagar Twitter yang viral dan konsep tagar viral sebagai media pendidikan karakter bagi netizen. Tujuan penelitian ini yaitu untuk mengetahui pola penggunaan tagar yang viral di media sosial Twitter dan juga untuk mengetahui konsep tagar viral sebagai media pembinaan karakter netizen. Penelitian ini memiliki manfaat untuk melengkapi konsep pendidikan karakter era teknologi dan membantu masyarakat menjadi netizen yang berkarakter. Penelitian menggunakan: pendekatan kualitatif; analisis wacana; objek penelitian berupa tagar viral; subjeknya adalah netizen; sampel berupa tagar #dajjal; observasi; catatan dokumen; analisis tinjauan pendidikan karakter; dan triangulasi teori. Hasil penelitian ini yaitu: 1) tagar viral digunakan untuk berbagi ilmu, berdoa, beropini, diskusi, gerakan sosial, mediator perdamaian, hiburan, dan kepentingan pribadi; 2) konsep pendidikan karakter bagi netizen yaitu tagar viral sebagai media penyampai pengetahuan nilai (values knowledge), ekspresi keyakinan nilai (values express), deklasari pilihan nilai (values declare), klarifikasi nilai (values clarification), aksi nilai (values action), dan pengontrol nilai (values control).Kata Kunci: Tagar, media, pendidikan karakter, netizen, Twitter